Pelatihan Pembelajaran PjBL Berbasis Alat Praktikum IPA Periskop di SMPN 3 Labuapi - Baiq Nabila Saufika Zainuri; Lalu Muhammad Rispan Sugi Saputra (Indonesian Journal of Education and Community Services, 2024)
Science education should emphasize providing students with direct, hands-on experiences to develop the competencies needed to explore and understand the natural world. Ultimately, this approach aims to help them discover subject matter concepts independently. One recommended instructional model for achieving competencies in attitudes, knowledge, skills, and critical thinking in science is the Project-Based Learning (PjBL) model. In this training program, Project-Based Learning was implemented through the creation of a simple practical tool: a periscope. The activity employed a community engagement method consisting of three steps: preparation, implementation, and evaluation. After the training session concluded, all participants were asked to complete a training evaluation questionnaire. This questionnaire aimed to assess the students' satisfaction level with the training. The questionnaire's evaluation indicators comprised two aspects, covering 14 questions. The results showed an average satisfaction rate of 83.74%. Therefore, it can be concluded that students strongly agree with the use of the learning media in the instructional process.